Efecto de aplicaciones foliares de molibdeno sobre el uso eficiente de nitrógeno y rendimiento en maíz amarillo duro - Zambrano Zambrano, Jandry Gabriel (2020)
The objective of this research was to prove the effectiveness of foliar applications of molybdenum on the efficient use of nitrogen and yield in hard yellow corn, which was developed at El Palmar site in Junín canton, Manabí. Therefore, four treatments with foliar application of Molybdenum were evaluated, of which one does not have a nitrogen dose and three have nitrogen fertilization doses which are: 100 kg ha-1,200 kg ha-1, 300 kg ha-1, which included a control without nitrogen omission. A randomized complete block design (DBCA) was established with five treatments and four replications, the factor being Nitrogen dose. The combination of the treatments and replicates results in 20 experimental units. The results showed that nitrogen fertilization increased the yield of the corn crop and that the highest agronomic efficiency of N was achieved with 100 kg of N ha-1.